Failure prediction and optimal selection of adhesives for glass/steel adhesive joints. (15th December 2019) - Katsivalis, Ioannis; Thomsen, Ole Thybo; Feih, Stefanie; Achintha, Mithila
Highlights: Ductility identified as main key factor for hybrid joint strength. Optimum combinations of strength/ductility exist for a given joint geometry. Maximum joint strength achieved for adhesives with intermediate strength/ductility. Developed FE methodology accurately predicts performance of hybrid adhesive joints. Abstract: Mild steel/tempered glass adhesive joints are becoming a common occurrence in the construction industry. A numerical parametric study for adhesive property optimisation is conducted and determines strength and ductility as the main parameters affecting the joint performance. Numerical simulations include adhesive pressure-sensitivity, plasticity and failure modelling and are also used to further investigate onset and progression of damage leading to failure of the joints. Following this, the market of structural adhesives is scanned, resulting in the identification of an adhesive system that aligns with the 'optimal' strength and ductility parameters identified from the parametric study. The chosen adhesive system is experimentally compared and benchmarked against a brittle and a ductile adhesive in steel/glass adhesive joints subjected to four different load-cases. It is demonstrated that the proposed modelling methodology yields accurate predictions of the adhesive and adherend stress states and failure behaviour for the four different load-cases, thus highlighting the model's ability to predict the response and failure of all three adhesives and tempered glass.